Female athlete research - combining science and practice - Mikkonen, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
The female athlete population includes several unique hormonal profiles (1). Some athletes are naturally menstruating, others use combined or progestin-only hormonal contraceptives, still others have menstrual disturbances ranging from sub-clinical to clinical and which may or may not be caused by low energy availability or the multistressor environment of elite sport. Where the three-step or two-step methods for identifying menstrual cycle phases or characterizing the hormonal profiles of naturally menstruating females are important for research striving to identify the influence of sex hormone concentrations and ratios on specific mechanisms or characteristics of sports performance (2,3), it is important to recognize that these methods are not appropriate for females that are not naturally menstruating. Furthermore, these laboratory methods are not easily applied to practice and are not necessarily feasible. As a universal blueprint for training according to a natural menstrual cycle phase does not exist, the need for menstrual cycle tracking for purposes beyond menstrual (and thereby physical) health are questionable. Nevertheless, monitoring the menstrual cycle (including ovulation) and hormonal contraceptive cycles and identification of patterns in symptoms or performance that may be related to changes in hormonal concentrations may be useful for athletes, coaches, and support staff like physicians as well as researchers. In practice, menstrual and hormonal contraceptive cycle monitoring are helpful for avoiding/identifying menstrual dysfunction and decreased health and performance that are often linked to low energy availability and relative energy deficiency in sport (4). In addition, menstrual and hormonal contraceptive cycle monitoring may allow us to modify approaches to training and/or nutrition if consistent negative patterns in subjective feelings around training or within performance emerge. Communication and collaboration are needed between science and practice to better inform research and practice. In addition, communication and collaboration with clinicians regarding ´the relationship between menstrual health and health and performance is important to best serve our female athletes and improve their (and clinician) body literacy. This presentation will highlight the variety in hormonal profiles that may be observed in the female athlete population and will present practical reasons for cycle tracking and reporting of / considering hormonal profiles in both research and practice including considerations for female athletes without natural/eumenorrheic cycles.